An Approach to John Rawls’ Normative Economic Though - Martínez Vallejo, Diego Fernando (Sociedad y Economía, 2015)
Rawls, since an early age, was interested in the normative principles of the modern eco- nomic thought, particularly in its welfare theory. This concern is not surprising. First, Rawls was always concerned about poverty and social class injustice. Both issues widely discussed in economics. Second, the development of the economic thought has been very close to the utilitarian history, Rawls’ greatest opponent. This paper presents the economic proposal of the Rawlsian theory, which in turn is shown as an alternative to the utilitarian approach. To do this, it emphasizes Rawls’ persistent concern for the un- derprivileged, and the importance the author gives to the market, as well as his proposals on tax and wages.